Effects of Probiotics on the Growth Performance, Antioxidant Functions, Immune Responses, and Caecal Microbiota of Broilers Challenged by Lipopolysaccharide - Yu, Yang; Li, Qing; Zeng, Xinfu; Xu, Yinglei; Jin, Kan; Liu, Jinsong; Cao, Guangtian (Frontiers in Veterinary Science, 2022)
We aimed to study the effects of dietary Bacillus coagulans (B. coagulans) and Lactobacillus plantarum (L. plantarum) on broilers challenged by Escherichia coli lipopolysaccharide (LPS). One-day-old Cobb chicks (360) were divided randomly into three treatments groups for 47 days: no supplementation (control, CON), B. coagulans supplementation (BC), and L. plantarum supplementation (LA). Broilers were intraperitoneally injected with 500 μg of LPS per kg body weight at 43, 45, and 47 days of age. At 1-21 days of age, the ADG in the BC and LA groups was higher than that in the CON group, and the feed to gain ratio (F/G) in the BC group was significantly decreased (P < 0.05). Compared with that in CON birds, the ADG was increased and the F/G was decreased in the BC and LA birds at 22-42 and 1-42 days of age, respectively (P < 0.05). After LPS stimulation, the endotoxin (ET), diamine oxidase (DAO), and D-lactic acid (D-LA) levels in the BC group were lower than those in the CON group (P < 0.05). The IgY, IgA, and IgM contents in the BC group and the IgY and IgM contents in the LA group were higher than those in the CON group (P < 0.05). The pro-inflammatory factor and interferon-β (IFN-β) contents (P < 0.05) decreased, and the anti-inflammatory factor content in the serum (P < 0.05) increased in the BC and LA groups. Compared with the CON and LA treatments, the BC treatment increased the concentrations of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT), and decreased that of malondialdehyde (MDA) (P < 0.05). In contrast with the CON treatment, the BC and LA treatments increased the abundance of Ruminococcaceae and reduced that of Desulfovibrio (P < 0.05). Moreover, BC increased the abundance of beneficial bacteria. Overall, supplementation with B. coagulans and L. plantarum promoted the growth of broilers, improved their immunity and antioxidant capacity, and alleviated the LPS-stimulated inflammatory response by regulating the intestinal flora.